Botulinum toxin type A ameliorates adjuvant-arthritis pain by inhibiting microglial activation-mediated neuroinflammation and intracellular molecular signaling. (30th April 2020) - Shi, Xiaojuan; Gao, Chengfei; Wang, Lin; Chu, Xiao; Shi, Qilin; Yang, Hui; Li, Tieshan
Abstract: Chronic inflammatory pain is a serious clinical problem caused by inflammation of the joints and degenerative diseases and greatly affects patients' quality of life. Persistent pain states are thought to result from the central sensitization of nociceptive pathways in the spinal dorsal horn. Spinal microglia-mediated neuroinflammation plays a pivotal role in the development and maintenance of the central sensitization of chronic inflammatory pain. Botulinum toxin type A (BoNT/A) was recently reported to have analgesic and anti-inflammatory effects. However, the precise mechanism underlying its analgesic effect remains unclear. Although several studies have reported that BoNT/A could regulate neuroflammation, the reduction of neuroinflammation regulated by BoNT/A in chronic inflammatory pain in experimentally induced arthritis has not been reported. The aim of this study was to investigate whether BoNT/A could alleviate adjuvant-arthritis pain via modulating microglia-mediated neuroinflammation and intracellular molecular pathway. The pain behavioral tests were performed before and after CFA immunization as well as after BoNT/A injection. Western blotting and immunofluorescence staining were used to assess the changes of microglial activation markers (ionized calcium binding adaptor molecule 1, IBA-1) and phosphorylation of P38MAPK (P-p38MAPK) in the lumbar spinal cord. TNF-αand P2X4R gene expression were studied by real-time reverse transcriptase-polymerase chain reaction (RT-PCR). The results showed that (1) the activation of spinal microglia can be continued till 21 days after CFA injection, which suggested its role in the development and maintenance of chronic inflammatory pain. (2) The intra-articular administration of a single eﬀective dose of BoNT/A (5U/10 U) on day 21 after CFA injection significantly reduced nociceptive behaviors and decreased protein overexpression and immunoreactivity for IBA-1 and P-p38MAPK in CFA induced rat. Simultaneously, BoNT/A (5 U) also inhibited the increase in TNF-α mRNA and P2X4R mRNA expression induced by CFA injection. These results suggested that BoNT/A is a potential therapeutic agent for relieving the neuroinflammation that occurs in chronic inflammatory pain by inhibiting the activation of microglial cells and the release of microglia-derived TNF-α. This effect is likely mediated by inhibiting the activation of the P2X4R–P38MAPK signaling pathways in spinal microglial cells. Highlights: A single intra-articular BoNT/A administration. Exerted an anti-nociceptive effect in a CFA-induced monoarthritis rat model. Decreased CFA-induced activation of spinal microglia and the upregulation of tumor necrosis factor-α. Modulated microglial activation-mediated neuroinflammation likely by inhibiting the intracellular P2X4R and P38MAPK signaling pathways.